The Effect of the Tax Planning to Firm Value with Moderating Board Diversity - Lestari, Nanik; Wardhani, Ratna (International Journal of Economics and Financial Issues, 2015)
The purpose of this research is to analyze the impact activities tax planning to firm value with board diversity as moderating variable. The research was conducted for non-banking and financial firms in Indonesia Stock Exchange for 2010 to 2011. The results of this study are: Firstly, we found evidence of positive relationship between tax planning and firm value. Secondly, we found evidence that board diversity (AGE and BSTUDY of member director) could increase the positive influence of tax planning into firm value, except for MINORITY could decrease the positive influence of tax planning into firm value. Finally, the results of the sensitivity test with the full model and the full sample suggested that tax planning had robust positive effect in increasing firm value, then the moderating influence of board diversity (BSTUDY and MINORITY) on the relationship between tax planning and firm value was consistent but other variables of board diversity (AGE) are not consistent. Keywords: Tax planning; Firm value; Board diversity. JEL Classifications: E21